2010
DOI: 10.1523/jneurosci.5464-09.2010
|View full text |Cite
|
Sign up to set email alerts
|

Calcium and Cyclic AMP Promote Axonal Regeneration in Caenorhabditis elegans and Require DLK-1 Kinase

Abstract: Axons of adult Caenorhabditis elegans neurons undergo robust regenerative growth after laser axotomy. Here we show that axotomy of PLM sensory neurons triggers axonal calcium waves whose amplitude correlates with the extent of regeneration. Genetic elevation of Ca2+ or cAMP accelerates formation of a growth cone from the injured axon. Elevated Ca2+ or cAMP also facilitates apparent fusion of axonal fragments and promotes branching to postsynaptic targets. Conversely, inhibition of voltage-gated calcium channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
344
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 275 publications
(365 citation statements)
references
References 48 publications
18
344
3
Order By: Relevance
“…Many of these studies have pushed these techniques a step further using image recognition and tracking techniques to enable recording from neurons in partially restrained or even freely moving animals as well as recording from multiple neurons simultaneously. Additional studies have investigated other aspects of calcium physiology such as the response to neuronal damage 13,20 as presented here as well as neuronal degeneration on longer time scales 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these studies have pushed these techniques a step further using image recognition and tracking techniques to enable recording from neurons in partially restrained or even freely moving animals as well as recording from multiple neurons simultaneously. Additional studies have investigated other aspects of calcium physiology such as the response to neuronal damage 13,20 as presented here as well as neuronal degeneration on longer time scales 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies combining laser microsurgery and C. elegans have identified how several factors, including animal age, neuronal type, synaptic branching and axon guidance signalling, influence regeneration [29][30][31] . Laser microsurgery screens, as well as screens using nematodes exhibiting spontaneous neurite breaks due to dysfunction of ÎČ-spectrin, have also revealed that axon regrowth depends on the activity of MAP kinase pathways [31][32][33] . Most recently, we have demonstrated the use of microfluidics in combination with femtosecond laser microsurgery to perform chemical screens on neural regeneration in C. elegans 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The injury-induced calcium outflow via RyR is crucial for stimulating both outgrowth and guidance of regenerating neurons (18). In C. elegans PLM sensory neurons, the amplitude of injury triggered calcium waves also correlates with the extent of regeneration (19). Whether calcium release from internal stores to sustain a back propagating calcium wave represents a specific property of regenerating neurons remains to be tested.…”
Section: Figmentioning
confidence: 99%